Desain Pembelajaran PAI Berwawasan Moderasi Beragama Untuk Membentuk Peserta Didik Yang Toleran dan Multikultural: Studi di MA Salafiyah Abu Hurairah Mataram - Rahman, Saofi (Universitas Hamzanwadi, 2026)
Islamic Religious Education (IRE) plays a strategic role in instilling moderate, tolerant Islamic values that are oriented towards multicultural life. This study aims to describe the design of religious moderation-oriented IRE at MA Salafiyah Abu Hurairah Mataram in shaping tolerant students who respect diversity. The research approach used a descriptive qualitative method with observation, interview, and documentation techniques. The results showed that the PAI learning design at MA Salafiyah Abu Hurairah Mataram was developed by integrating religious moderation values into every component of learning, from planning and implementation to evaluation. Teachers play an active role in creating a dialogical, inclusive, and contextual learning atmosphere. The learning strategies used emphasize value reflection, social case studies, and religious project-based learning that fosters mutual respect. Thus, the PAI learning design with a religious moderation perspective has proven to be effective in shaping the character of students to be tolerant and multicultural.